Study of the Absorptance of Si-gratings and of arrays of SiO2-filled trenches on Si-grating substrate - Ghmari, Faouzi; Mezni, Ilhem (JOURNAL OF ADVANCES IN PHYSICS, 2016)
The purpose of this paper is to study the radiative properties of two model structures. The first model (A-1) is a rectangular grating of silicon (Si). The second one (A-2) is obtained from A-1 by filling their trenches by SiO2. These patterned wafers are characterized by three geometrical parameters, the period d, the filling factorand the thickness h. To derive and compute the radiative properties we use a rigorous coupled wave analysis (RCWA) method. Our attention is focused on the absorptance of these structures when they are illuminated by a monochromatic plane wave. We investigate the effect of the filling factor on the absorptance versus the direction of the incident wave. At specific angles of incidence the effect of the period is also studied. Besides, the influence of the thickness h on the absorptance is included throughout this work. At the wavelength = 632,8nm, we especially show that we can identify several perfect absorber model structures characterized by specific parameters and by accurate angle of incidence. We show that this will be done in both transverse electric (TE) and transverse magnetic (TM) polarization cases.